How Styles of Conflict Management Apply by Managers at Workplace? With Concerns of Different Theories and Views - Mehrad, Aida (International Journal For Research In Educational Studies, 2019)
Recognizing the workplace and its atmosphere can be more imperative part in organizational and industrial psychology, also this fact in most of the management fields area considered, comprehensively. Examining effective factors that increase or decrease the level of work outcomes and change the feeling and performance of staff and managers at the workplace assumed more critical. Likewise, distinguishing operative factors that help and support managers at work to cope with issues and difficulties that maybe occur during work, is valuable and crucial. Conflict be situated as one of these important factors that can appear in any workplaces, and it's avoidable. In this regard, recognizing the conflict as one of the main organizational factors and the ways of control and solve it, is very important. Furthermore, in the present literature review, the researcher endeavoured to clarify the conflict and applying styles of its management via managers at the workplace. These styles comprised Accommodating, Avoidance, Collaboration, Competing, and Compromising that have practical applications in the management area. The literature review has likewise shown that various theories and views towards a conflict that have been explained in dissimilar decades through diverse theorists, psychologists and sociologist. In conclusion, based on exploring various styles of conflict management in a diverse situation; similarly, applying and considering different methods, the researcher explained that we cannot ignore or reject any styles of conflict management because each of them is beneficial, if managers improve their knowledge and identify the exact situation, they can apply the correct style. Moreover, through using precise style, managers and staff can observe a peaceful work environment and high level of work outcomes in work duration.